PENINGKATAN PRODUKTIVITAS RUMPUT RAJA MELALUI APLIKASI TEKNOLOGI BUDIDAYA YANG RAMAH LINGKUNGAN - Suarna, I Wayan (Bumi Lestari, 2012)
The experiment of sustainable technology application with casting organic fertilizer and styloassociation with King grass was conducted at Siut Cattle farm at Gianyar regency. The experimentdesign was a randomized block design arranged in Split-plot pattern and was replicated threetimes. The treatment consisted of two factors as follows: (1) two types of cropping systems as mainplot (King grass monoculture and King grass – stylo association), (2) four levels of casting organicfertilizer as sub-plot (0, 10, 20, dan 30 t ha -1). The variable studied were: forage production,production characteristic, and leaf characteristic. Leaf characteristic variable consisted of: leafarea, leaf color, and leaf thickness. The results showed that: casting organic fertilizer weresignificantly (P<0.05) effect on leaf area and leaf production. Cropping system was not significantly(P>0.05) effect on all of variable studied. There was no significantly interaction (P>0.05) foundedbetween cropping system and casting organic fertilizer on all of variable studied. The conclusion ofthese experiment were: casting application at King grass and its association with stylo wasincreased forage production at first regrowth. The optimal levels of casting organic fertilizer in Kinggrass monoculture and that association with stylo were 17.09 dan 16.41 t ha -1 respectively.
Keywords: Casting, association, productivity